MANAJEMEN PROGRAM PENDIDIKAN KESETARAAN PAKET C DI SPNF SANGGAR KEGIATAN BELAJAR (SKB) BALIKPAPAN UTARA KALIMANTAN TIMUR - Adawiyah, Robyathul; Latif, M. Ali; Asri, Muhammad (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study examines the management of the C package education program at the SPNF Learning Activity Center (SKB) in North Balikpapan, East Kalimantan. The purpose of this study was to find out how the management of the C package education program at SPNF was the Learning Activity Center (SKB) in North Balikpapan, East Kalimantan. The Learning Activity Center (SKB) is a form of educational institution that provides services to the community. The problem in this research is how to manage the package C equivalence education program. The aims of this research are to describe: 1) package C program planning, 2) package C program organization, 3) package C program implementation, and 4) package C program evaluation. This study uses a qualitative approach with descriptive methods, data collection techniques are carried out by observation, interviews, and documentation. The informants consisted of the Head of SKB, 1 tutor, and 3 learning residents. Data analysis techniques used in this study include: 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion/verification. The technique used to check the validity of the data in this study is source and data triangulation. From the research results, the conclusions were obtained, namely: 1) planning, the package C program at the North Balikpapan SKB was in accordance with the direction of the Balikpapan city education office but was still adjusted to the needs of students, 2) the organization of the North Balikpapan SKB could not be said to be good because the institution was still lack of quality and quantity of tutors, 3) implementation of the package C program at North Balikpapan SKB learning process, learning resources, learning methods used in learning adapted to the needs of students. 4) evaluation of the C package program is carried out using a formative evaluation which is carried out when one chapter of the module is completed, summative evaluation is carried out at the end of each semester and the final evaluation is a school exam.